2016
DOI: 10.1016/j.nedt.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Understanding pre-registration nursing fitness to practise processes

Abstract: Diverse fitness to practise processes are currently in place for Scottish pre-registration nursing students. These processes draw on a shared set of principles but are couched in different terminology and vary according to their location within different university structures. Nevertheless, universities appear to be confronting broadly similar issues around ensuring fitness to practise and are building a body of expertise in this area. Examples of good practice are identified and include the use of staged proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Registration with professional bodies serves several important functions, and helps to assure the registered individuals are fit to practice medicine [25]. Maintaining a contemporaneous registry of qualified doctors facilitates simultaneous control of entry to the register of recognized physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Registration with professional bodies serves several important functions, and helps to assure the registered individuals are fit to practice medicine [25]. Maintaining a contemporaneous registry of qualified doctors facilitates simultaneous control of entry to the register of recognized physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, UK HEIs have developed various strategies to meet these requirements (Unsworth 2011). A study of Scottish HEIs' FtP processes identified examples of good practice in the monitoring of FtP (Haycock-Stuart et al 2014, MacLaren et al 2016, but also revealed that HEIs have encountered significant challenges around FtP, and that there are gaps in current knowledge about FtP and pre-registration nursing students, including how students and mentors understand and experience FtP processes.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large policy literature relating to FtP and the regulation of health and social care practitioners, although standards, advice, and guidance on FtP for health and social care students vary as to detail and devolution to HEIs (Haycock-Stuart et al 2014, MacLaren et al 2016. In contrast, there is little empirical published research pertaining to FtP and preregistration nursing students, and literature reviews by Jomeen et al (2008) and Boak et al (2012) identify that much of the existing FtP literature consists of literature reviews and descriptive or discursive papers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians and nurses should try to reduce the barriers using various innovative ways of education and at the end, they have to be ensured that patients have got appropriate understanding (30,31). Providing education for both patients and their families is a main responsibility of medical team members, especially nurses (30).…”
Section: Introductionmentioning
confidence: 99%